Human Papillomavirus and Related Diseases From Bench to Bedside a Diagnostic and Preventive Perspective 2013
DOI: 10.5772/55810
|View full text |Cite
|
Sign up to set email alerts
|

Modern Molecular and Clinical Approaches to Eradicate HPVMediated Cervical Cancer

Abstract: Additional information is available at the end of the chapter http://dx.doi.org/10.5772/55810 . IntroductionCervical cancer was formerly the second most common cancer killer of women worldwide. Following widespread adoption of Papanicolau cytologic screening Pap test for cervical cancer in the s, this began to change. Today, advanced cervical cancer is rare in screened populations. Although an uncommon disease in developed nations, internationally about , women annually are diagnosed with cervical cancer, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 185 publications
(204 reference statements)
0
1
0
Order By: Relevance
“…An organized prevention program is frequently reported to be needed for reducing the rate of cervical cancer in low and middle income countries ( 56 ). It is frequently reported that considerable number of females diagnosed with cervical cancer have never been screened by HPV testing or they may even be asymptomatic patients ( 39 , 58 - 60 ). Human Papillomavirus infection is diagnosed mainly by molecular methods and can be either DNA-based or RNA assays.…”
Section: Discussionmentioning
confidence: 99%
“…An organized prevention program is frequently reported to be needed for reducing the rate of cervical cancer in low and middle income countries ( 56 ). It is frequently reported that considerable number of females diagnosed with cervical cancer have never been screened by HPV testing or they may even be asymptomatic patients ( 39 , 58 - 60 ). Human Papillomavirus infection is diagnosed mainly by molecular methods and can be either DNA-based or RNA assays.…”
Section: Discussionmentioning
confidence: 99%